Defect induced ferromagnetism in MgO and its exceptional enhancement upon thermal annealing: a case of transformation of various defect states. Issue 19 (26th April 2017) - Pathak, Nimai; Gupta, Santosh Kumar; Prajapat, C. L.; Sharma, S. K.; Ghosh, P. S.; Kanrar, Buddhadev; Pujari, P. K.; Kadam, R. M.
Abstract : Micron size MgO particles showed various defect induced ferromagnetism with an exceptional enhancement upon thermal annealing due to transformation of one kind of cluster vacancy to another. Abstract : MgO particles of few micron size are synthesized through a sol–gel method at different annealing temperatures such as 600 °C (MgO-600), 800 °C (MgO-800) and 1000 °C (MgO-1000). EDX and ICP-AES studies confirmed a near total purity of the sample with respect to paramagnetic metal ion impurities. Magnetic measurements showed a low temperature weak ferromagnetic ordering with a T C (Curie temperature) around 65 K (±5 K). Unexpectedly, the saturation magnetization ( M s ) was found to be increased with increasing annealing temperature during synthesis. It was observed that with J = 1 or 3/2 or S = 1 or 3/2, the experimental points are fitted well with the Brillouin function of weak ferromagnetic ordering. A positron annihilation lifetime measurement study indicated the presence of a divacancy (2VMg + 2VO ) cluster in the case of the low temperature annealed compound, which underwent dissociations into isolated monovacancies of Mg and O at higher annealing temperatures. An EPR study showed that both singly charged Mg vacancies and oxygen vacancies are responsible for ferromagnetic ordering. It also showed that at lower annealing temperatures the contribution from was very low while at higher annealing temperatures, it increased significantly. A PL study showed that most of the F + centers were present in their dimer form, i.e. as centers. DFT calculation implied that this dimer form has a higher magnetic moment than the monomer. After a careful consideration of all these observations, which have been reported for the first time, this thermally tunable unusual magnetism phenomenon was attributed to a transformation mechanism of one kind of cluster vacancy to another.